Desires, Need, Perceptions, and Knowledge of Assisted Reproductive Technologies of HIV-Positive Women of Reproductive Age in Ontario, Canada. (16th August 2012) - Zhang, Yimeng; Margolese, Shari; Yudin, Mark H.; Raboud, Janet M.; Diong, Christina; Hart, Trevor A.; Shapiro, Heather M.; Librach, Cliff; Gysler, Matt; Loutfy, Mona R.
Abstract : The purpose of this cross-sectional study is to assess the desire, need, perceptions, and knowledge of assisted reproductive technologies (ARTs) for women living with HIV (WLWHIV) and determine correlates of ART knowledge desire. WLWHIV of reproductive age were surveyed using the survey instrument "The HIV Pregnancy Planning Questionnaire" at HIV/AIDS service organizations across Ontario, Canada. Of our cohort of 500 WLWHIV, median age was 38, 88% were previously pregnant, 78% desired more information regarding ART, 59% were open to the idea of receiving ART, 39% felt they could access a sperm bank, and 17% had difficulties conceiving (self-reported). Age, African ethnicity, and residence in an urban center were correlated with desire for more ART information. Of participants, 50% wanted to speak to an obstetrician/gynecologist regarding pregnancy planning, and 74% regarded physicians as a main source of fertility service information. While the majority of participants in our cohort desire access to ART information, most do not perceive these services as readily accessible. Healthcare practitioners were viewed as main sources of information regarding fertility services and need to provide accurate information regarding access. Fertility service professionals need to be aware of the increasing demand for ART among WLWHIV.